The Ijtihad Pada Era Kontemporer: Ijtihad Para Era Kontemporer - Muhammad Imron; Tri Wahyu Hidayat (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This article examines the definition of ijtihad, the law of ijtihad, the division of ijtihad, the method of ijtihad, the requirements of mujtahid, the characteristics of contemporary ijtihad, and examples of the application of ijtihad in the contemporary era. As for the discussion of examples of the application of ijtihad methods in contemporary cases, the author takes the example of